Nature's blueprint for business : harnessing the hidden power of edges - Garcia, Ines (Agile coach) (Routledge, 2026)
Tapping into proven strategies, mechanisms and patterns that have been fine-tuned over 3.8 billion years, this book bridges the gap between the natural world and the business world and explores how to develop resilient organizations and businesses using lessons from nature.The science of biomimicry is an emerging force in helping us to gaze afresh at the world around us, often inspiring technological inspiration, but we have been slow to look at the organizational and relationship models that are all around us. This book contends that natural abundance flourishes at the edges, where one environmental element contacts another, and that these relationships that have been successful for millennia have endless lessons for us about how we organize ourselves. Each chapter starts with a clear example of a problem that a team or organization might face, goes on to consider a range of natural examples and offer practical suggestions to incorporate nature's wisdom in the business world, and concludes with success stories of people and organizations already embracing the principles outlined in the book. Employing these principles and aided by suggested activities, readers will develop personalized plans, tailored to their unique situations, to lead their teams' evolution into thriving organizations.Observing edges, spaces and boundaries shows that is these are where magic happens-and with this book, leaders of all types of teams and organizations will be empowered to make real and immediate changes in their own contexts.